Comparison of gene expression in human periodontal ligament cells cultured from teeth immediately after extraction and from teeth cryopreserved for 1 week - Min, Kyung-San; Lee, Hyeon-Woo; Lee, Hee-Su; Lee, Jeong-Ho; Park, Sang Hyuk (Cryobiology, 2010)
Gene expression was compared by cDNA microarray analysis in human periodontal ligament (PDL) cells cultured from teeth immediately after extraction and from teeth cryopreserved for 1 week. Twenty healthy collateral premolar teeth without caries and restorations were obtained from 10 young patients, one maxillary and one mandibular premolar from each subject. The teeth from five patients, from two patients, and from three patients out of total 10 patients were used for cDNA microarray assay, for RT-PCR, and for real-time PCR, respectively. One premolar was used immediately after extraction (control), and another premolar was stored in liquid nitrogen at −196 °C for 1 week (cryopreserved) from each patient. PDL cells from these teeth were cultured separately through three passages. Total RNA was isolated and gene expression was compared between the cells from control and cryopreserved group out of each subject. The microarray data were validated using the reverse transcription-polymerase chain reaction (RT-PCR) and confirmed by quantitative real-time PCR. The cultured PDL cells from the control and cryopreserved teeth were of similar appearance under an optical microscope. In all subjects the fibroblast growth factor receptor 2 (FGFR2) gene was downregulated in the cells from the cryopreserved tooth. This study shows that cryopreservation of teeth affects the expression of the FGFR2 gene in cultured PDL cells, which is related to cell growth, cell development, and cell–cell signaling.